2020
DOI: 10.15376/biores.16.1.979-986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylanase pretreatment on the kraft pulping of poplar

Abstract: This study aimed to determine the influence of prehydrolysis of wood chips on the kraft pulping of Populus x euramericana. Optimum cooking conditions were determined by evaluating different alkali concentrations and cooking periods. Xylanase was used to hydrolyze chips before cooking. Prehydrolysis process increased the yield and viscosity of pulp. Consequently, the mechanical properties of paper changed remarkably. In contrast, the optical properties of the unbleached kraft pulp declined due to lignin content. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The xylanase hydrolyzed the xylan, caused the separation of the secondary wall, and increased the surface area by fibrillation, which improved the fiber-to-fiber bonding. The improved fiber-to-fiber bonding may have improved the physical strength properties (Akgül et al 2021;Kumar et al 2021). The FE-SEM analysis of the pulp samples also indicated that there was improved fiber bonding for the destructured-xylanase treated pulp samples (Fig.…”
Section: Effect Of Mechanical and Xylanase Pretreatment On Strength Propertiesmentioning
confidence: 89%
See 4 more Smart Citations
“…The xylanase hydrolyzed the xylan, caused the separation of the secondary wall, and increased the surface area by fibrillation, which improved the fiber-to-fiber bonding. The improved fiber-to-fiber bonding may have improved the physical strength properties (Akgül et al 2021;Kumar et al 2021). The FE-SEM analysis of the pulp samples also indicated that there was improved fiber bonding for the destructured-xylanase treated pulp samples (Fig.…”
Section: Effect Of Mechanical and Xylanase Pretreatment On Strength Propertiesmentioning
confidence: 89%
“…The decreased screened pulp yield and reduced Kappa number indicated that there was better xylanase penetration, and it acted on the xylan. The xylanase treatment hydrolyzed the xylan, broke down the lignincarbohydrate bonds, and opened the polymer to facilitate the removal of lignin by white liquor during pulping and decreased the Kappa number of resultant pulp (Akgül et al 2021;Gautam et al 2021). Varghese et al (2020b) performed a xylano-pectinolytic enzyme pretreatment of sugarcane bagasse before soda-anthraquinone pulping.…”
Section: Xylanase Treatmentmentioning
confidence: 99%
See 3 more Smart Citations